Inflation Targeting Under Imperfect Policy Credibility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper presents a model for Inflation Targeting under imperfect policy credibility. It modifies the conventional model in three ways: an endogenous policy credibility process, by which monetary policy can gain or lose credibility over time; non-linearities in the inflation equation and in the credibility generating process; and an explicit loss function. The model highlights problems associated with the practice of setting a series of rigid near-term inflation targets. Also, unfavorable supply shocks pose a difficult problem: an appropriate response involves an interest rate increase, some loss of output, and a period of increased inflation. A delayed response can result in a prolonged period of stagflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet